Reliability, usefulness, and validity of the 30-15 intermittent ice test in young elite ice hockey players - Buchheit, M.; Lefebvre, B.; Laursen, P. B.; Ahmaidi, S. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the reliability, usefulness, and validity of the 30-15 Intermittent Ice Test (30-15IIT) in 17 young elite ice hockey players. For the reliability and usefulness study, players performed the 30-15IIT 7 days apart. For the validity study, data derived from the first 30-15IIT were compared with those obtained from the 30-15 Intermittent Fitness Test (30-15IFT, the running version of this test used as a reference marker for its ability to assess cardiovascular fitness in the field, that is, Vo2peak). Maximal speed, heart rate at exhaustion (HRpeak) and postexercise blood-lactate levels ([La]b) were collected for all tests, whereas submaximal HR was taken at stages 4 and 8 (HRstage4 and HRstage8) during the 30-15IIT. All intra-class correlation coefficients were >0.94. Coefficients of variation were 1.6% (90% CI, 1.3-2.3), 1.7% (1.3-2.8), 1.4% (1.0-2.2), and 0.7% (0.5-1.1) for maximal skating speed, HRstage4, HRstage8, and HRpeak, respectively. Correlations between maximal velocities and HRpeak obtained for the 30-15IIT vs. 30-15IFT were very large (r = 0.72) and large (r = 0.61), respectively. Maximal skating speed was also largely correlated to estimated Vo2peak (r = 0.71). There was however no correlation for [La]b values between both tests (r = 0.42). These results highlight the specificity of the on-ice 30-15IIT and show it to be a reliable and valid test for assessing cardiorespiratory fitness in young elite players. Coaches could interpret a change in performance of at least 2 stages, or a change in submaximal HR of more than 8% (˜8 b/min) during the eighth stage to be a meaningful change in skating fitness.